Mass measurement of Re-190. (6th July 2020) - Griffiths, M R; Wheldon, C; Kokalova, Tz; Turner, A; Pirrie, S; Ziman, V; Ashwood, N I; Malcolm, J D; Barr, M; Freer, M; Faestermann, Th; Wirth, H-F; et al.
Abstract: In this paper, a measurement of the atomic mass and mass excess of Re 75 190 are presented. This isotope and Ir 77 192 were produced at the Maier-Leibnitz Laboratory (MLL) in Munich in the 192 Os( d, α ) 190 Re and 194 Pt( d, α ) 192 Ir reactions. The Q3D magnetic spectrograph was used to measure the momenta of the α -particle ejectiles in order to reconstruct states in both 190 Re and 192 Ir. A mass calibration was performed using known energy levels in 192 Ir. These measurements were used to obtain a new value of the mass excess of 190 Re, −35583 ± 5 keV. The previously known literature value is −35640 ± 70 keV.